When is Growth Pro-Poor? : Cross-Country Evidence - Kraay, Aart (IMF Working Papers; Working Paper ;, 2004)
Growth is pro-poor if the poverty measure of interest falls. This implies three potential sources of pro-poor growth: (a) a high rate of growth of average incomes; (b) a high sensitivity of poverty to growth in average incomes; and (c) a poverty-reducing pattern of growth in relative incomes. I empirically decompose changes in poverty in a large sample of developing countries into these components. In the medium run, most of the variation in changes in poverty is due to growth, suggesting that policies and institutions that promote broad-based growth should be central to pro-poor growth. Most of the remainder is due to poverty-reducing patterns of growth in relative incomes, rather than differences in the sensitivity of poverty to growth in average incomes. Cross-country evidence provides little guidance on policies and institutions that promote these other sources of pro-poor growth.